Improving Learning Outcomes and Learning Motivation of Students Through Teams Games Tournament Learning Model (TGT) - Rahayu Febri Riyanti; Suranto Suranto; Norazmie Yusof; Amalia Febriyanti (Jurnal VARIDIKA, 2024)
This research investigates the impact of the problem-based learning (PBL) model on enhancing students' critical thinking abilities within civic education in third-grade classes at SDN Srewendari, Malang City. The study aims to assess the influence of the PBL approach on students' proficiency in analyzing facts, articulating reasons and arguments, drawing conclusions, and effectively presenting their findings. Employing a quasi-experimental design with the Nonequivalent Groups Pretest-Posttest Control Group methodology, the research compares the average post-test scores of critical thinking skills between the experimental and control groups through a t-test. The study population comprises third-grade students from SDN Srewendari, Malang City, with the sample consisting of experimental class IIIa and control class IIIb. Data collection involves observation, utilizing rating scale instruments, and assessments comprising test or evaluation questions administered during class sessions. The analysis is conducted descriptively and quantitatively, employing a difference test with a confidence level exceeding 95%. Findings indicate a positive and statistically significant impact of the problem-based learning model on students' critical thinking skills within civic education.